European and Latin American Thought in Dialogue: Keys for Social and Ethics Training - Ortega Cabrera, Agustín (2020)
In this article we develop our presentation presented at the XVII National Congress of Philosophy, “Critical reflection, teaching of Philosophy and crisis of humanity” (Huánuco 2019), entitled: “European thought, personalism and Latin American philosophy. Contributions for a social ethic in a solidary and integral humanism ”. We expose the dialogue and encounter between a series of currents of thought and culture inspired by faith such as European or Western, the labor movement, personalism or Latin American thought with its theological background; with authors such as E. Mounier, G. Rovirosa, I. Ellacuría, etc. Which provides us with keys and guidelines for a social thought, a culture of solidarity and ethics manifested in an integral humanism that enables a critical, liberating and transforming education-training. In this sense, it is about promoting values and principles such as solidarity, peace, justice, interculturality, integral ecology together with good living that guide a critical and transformative formative-pedagogical paradigm or model.